Gender, ethnic, and socioeconomic differences in access to catheter ablation therapy in patients with atrial fibrillation - Hamade, Hani; Jabri, Ahmad; Mishra, Pooja; Butt, Muhammad Umer; Sallam, Sherin; Karim, Saima (Frontiers in Cardiovascular Medicine, 2023)
Introduction Female patients, patients from racial minorities, and patient with low socioeconomic status have been noted to have less access to catheter ablation for atrial fibrillation. Methods This is a cross-sectional, retrospective study using a large population database (Explorys) to evaluate the gender, racial and socioeconomic differences in access of catheter ablation therapy in patient with atrial fibrillation. Results A total of 2.2 million patients were identified as having atrial fibrillation and 62,760 underwent ablation. Females had ablation in 2.1% of cases while males received ablation in 3.4% of cases. Caucasians had ablation in 3.3% of cases, African Americans in 1.5% of cases and other minorities in 1.2% of cases. Individuals on medicaid underwent ablation in 1.6% of cases, individuals on medicare and private insurance had higher rates (2.8 and 2.9%, respectively). Logistic regression showed that female patients (OR 0.608, CI 0.597–0.618, p < 0.0001), patients who are African American (OR 0.483, CI 0.465–0.502, p < 0.0001), or from other racial minorities (OR 0.343, CI 0.332–0.355, p < 0.0001) were less likely to undergo ablation. Patient with medicare (OR 1.444, CI 1.37–1.522, p < 0.0001) and private insurance (OR 1.572, CI 1.491–1.658, p < 0.0001) were more likely to undergo ablation. Conclusion Female gender, racial minorities, low socioeconomic status are all associated with lower rates of catheter ablation in management of atrial fibrillation.